Successful deliveries in a case of spontaneous pregnancy in ‘uterus bicornis unicollis’ with dicavitory twin gestation: a rare case report - Sureddi, Priyanka Koteswararao; Dalmia, Rachana Deepak; Tambvekar, Sunil Eknath; Athavale, Umesh Vishnu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Congenital anomalies of the uterus cervix and vagina are caused by alterations in development or fusion of the Mullerian ducts and are associated with multiple obstetric problems. A 32-year-old primigravida presented with spontaneous conception of dichorionic diamniotic twin with one twin in the right horn and another in the left horn of a bicornuate uterus. At 31.4 weeks of gestation the patient presented with preterm premature rupture of membranes followed by preterm labour, and progressed to deliver vaginally, resulting in the successful delivery of a live twin male and female baby. Spontaneous twin pregnancies in case of uterus bicornis unicollis are reported rarely. Here we discuss an extremely rare occurrence of spontaneous dicavitatory twin pregnancy in uterus bicornis unicollis and its outcome.